2011
DOI: 10.1007/s00056-011-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Overjet correction and space closure mechanisms for Class II treatment by extracting the maxillary first molars

Abstract: Overjet correction was essentially achieved by a retrusion of the upper incisors, as well as by ventral growth of the lower jaw and protrusion of the lower incisors. Space closure was only partly achieved by distalization of the premolars.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
6
0
1
Order By: Relevance
“…Previous analysis of overjet correction with the same low-friction appliances in bilateral M1 extraction cases showed that approximately one-third of the anteroposterior correction was achieved by protrusion of the mandibular incisors. 19 With reference to the skeletal measurements, we found a statistically significant increase in lower-face vertical dimension in the treated subjects. However, the 0.1%-0.5% increase in the ratio of lower anterior facial height to total anterior facial height between time points can be considered clinically irrelevant.…”
Section: Discussionmentioning
confidence: 94%
“…Previous analysis of overjet correction with the same low-friction appliances in bilateral M1 extraction cases showed that approximately one-third of the anteroposterior correction was achieved by protrusion of the mandibular incisors. 19 With reference to the skeletal measurements, we found a statistically significant increase in lower-face vertical dimension in the treated subjects. However, the 0.1%-0.5% increase in the ratio of lower anterior facial height to total anterior facial height between time points can be considered clinically irrelevant.…”
Section: Discussionmentioning
confidence: 94%
“…A systematic review by Kouvelis et al [ 19 ] found no significant differences between premolar extraction (Ex) and non-extraction treatment (Nonex) regarding vertical parameters in ten out of fourteen studies. Significant increases were found in Nonex for N-Me (Ex: +1.5 mm; Nonex: +5.5 mm; p < 0.05) [ 15 ] and for SN^GoGn (Ex: −0.9°; Nonex: +0.8°; p < 0.05) [ 16 ], but without concurrent changes in other vertical measurements. Two other studies showed opposite effects on N-Me (Ex: +2.3 mm; Nonex: +0.9 mm; p < 0.05) [ 20 ] and FMA (Ex: +0.3°; Nonex: −2.0°; p < 0.05) [ 21 ], indicating that vertical parameters increased more in extraction cases.…”
Section: Discussionmentioning
confidence: 99%
“…Class II extraction treatment carries the risk of proclination of the lower incisors and loosing upper incisors’ root torque control with consequent poor overjet and overbite correction, compromised lateral intercuspation and incomplete closure of the extraction spaces [ 28 ]. Booij et al showed, in Class II patients treated with maxillary first molar extractions, that the overjet reduction of 5.2 mm in total was achieved by skeletal changes (1.7 mm) expressed as dorsal movement of point A and forward movement of point Pg and by dental changes (3.5 mm) as retrusion of upper incisors and protrusion of lower incisors [ 15 ]. The present results agree with the previously discussed ones, as the inclination of upper incisors over SN reduced indeed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the Sagittal Occlusal analysis (SO) according to Pancherz. 14,16 The lower incisor inclination (L1L/ML) increased significantly during treatment by 5.43° (95% CI 4.29-6.56; p < 0.001) and remained stable in the post-treatment period, probably because of the fixed retainers. This rather large proclination likely resulted from levelling of the curve of Spee and the use of Class II elastics.…”
Section: Dentoalveolar Changesmentioning
confidence: 99%